2019
DOI: 10.1051/matecconf/201928602008
|View full text |Cite
|
Sign up to set email alerts
|

Numerical study of the effect of concrete cover and the friction of steel concrete interface

Abstract: The work presented in this paper resume a numerical analysis of the concrete cover effect, on the resistance of the steel-concrete interface. The effect of friction on the interface behavior is also included. For this, a brief description of the experimental steps generally used for the characterization of the steel-concrete interface is presented. Also, the CDP model, Concrete Damage Plasticity, is illustrated. The results of the numerical simulation using the Abaqus code are presented with different diameter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 3 publications
0
1
0
Order By: Relevance
“…The stability depends on the cohesion at the interface between the concrete and the steel reinforcement, which can be evaluated by measuring the maximum value of pulling force and by studying behavior of the composite during the pull-out test. In fact, several experimental and numerical studies have been carried out over the last decade to assess the adhesion between steel and concrete under severe conditions of mechanical and thermal loading, for example the work of [9][10][11][12][13][14][15]. These studies have revealed that concrete presents a good performance regarding its fire resistance thanks to all the physicochemical characteristics that concrete presents, such as its strength especially to compression, its low thermal diffusion etc.…”
Section: Introductionmentioning
confidence: 99%
“…The stability depends on the cohesion at the interface between the concrete and the steel reinforcement, which can be evaluated by measuring the maximum value of pulling force and by studying behavior of the composite during the pull-out test. In fact, several experimental and numerical studies have been carried out over the last decade to assess the adhesion between steel and concrete under severe conditions of mechanical and thermal loading, for example the work of [9][10][11][12][13][14][15]. These studies have revealed that concrete presents a good performance regarding its fire resistance thanks to all the physicochemical characteristics that concrete presents, such as its strength especially to compression, its low thermal diffusion etc.…”
Section: Introductionmentioning
confidence: 99%